A novel louvered fin design to enhance thermal and drainage performances during periodic frosting/defrosting conditions. (15th February 2016) - Kim, Min-Hwan; Kim, Hisuk; Kim, Dong Rip; Lee, Kwan-Soo
Highlights: Thermal and drainage performances of a novel design louvered fin were investigated. The thermal performance of the asymmetric fin was improved in the re-frosting cycle. The asymmetric louvered fin exhibited better drainage on the leading edge of fins. Lower surface tension between fin surface and water droplet improved the drainage. Abstract: The retention water on fin surface can significantly degrade the thermal performance of heat exchangers under periodic frosting/defrosting conditions, which also leads to a decrease in the energy efficiency of air-source heat pumps. A novel louvered fin design was suggested to improve the drainage and the thermal performance of heat exchanger. The novel louvered fin had an asymmetric louver arrangement by flattening two louvers on the leading edge. The retention water formed on fin surface markedly decreased the heat transfer rate of the conventional symmetric louvered fins in re-frosting cycles. On the other hand, the asymmetric louvered fins improved the drainage performance of the retention water, which enhanced the heat transfer rate. To identify the reason of the difference in drainage performance between two fin geometries, additional experiments were carried out with enlargement models. The improvement in drainage performance of the asymmetric fin design originated from the lowered surface tension between the fin surface and water droplet.